2007
DOI: 10.1088/0264-9381/24/8/002
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniqueness in conformal formulations of the Einstein constraints

Abstract: Standard methods in non-linear analysis are used to indicate that there exists a parabolic branching of solutions of the LichnerowiczYork equation with an unscaled source. We also apply these methods to the extended conformal thin sandwich formulation and, by assuming that the linearised system develops a kernel solution for sufficiently large initial data, we reproduce the parabolic solution curves for the conformal factor, lapse and shift found numerically by Pfeiffer and York.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 21 publications
0
58
0
Order By: Relevance
“…Above ω ¼ 0.01625M −1 ⊙ , the initial data code fails to converge. The steepening of the χ vs ω curve is reminiscent of features related to the nonuniqueness of solutions of the extended conformal thin sandwich equations [45,[50][51][52], and it is possible that our failure to find solutions originates in an analogous breakdown of the uniqueness of solutions of the constraint equations. For S-.5z, we achieve an accuracy of ∼10 −7 , whereas for S.4z and S.4x, the accuracy is ∼10 −4 due to finite L. While the focus of our investigation lies on rotating NS, we note that for ω ¼ 0 our data sets reduce to the standard formalism for irrotational NS.…”
Section: Quasilocal Spinmentioning
confidence: 99%
“…Above ω ¼ 0.01625M −1 ⊙ , the initial data code fails to converge. The steepening of the χ vs ω curve is reminiscent of features related to the nonuniqueness of solutions of the extended conformal thin sandwich equations [45,[50][51][52], and it is possible that our failure to find solutions originates in an analogous breakdown of the uniqueness of solutions of the constraint equations. For S-.5z, we achieve an accuracy of ∼10 −7 , whereas for S.4z and S.4x, the accuracy is ∼10 −4 due to finite L. While the focus of our investigation lies on rotating NS, we note that for ω ¼ 0 our data sets reduce to the standard formalism for irrotational NS.…”
Section: Quasilocal Spinmentioning
confidence: 99%
“…Therefore, assessing wheter or not the scalar equations (15) and (16) present the good signs for the application of a maximum principle is an important step for understanding the uniqueness properties of the whole system. However, as pointed out in the previous section, the CFC equations for the conformal factor and the lapse possess the wrong signs in the quadratic extrinsic curvature terms (once everything is expressed in terms of the lapse and the shift).…”
Section: The New Scheme In the Conformally Flat Casementioning
confidence: 99%
“…In section 2 we study the solution branches of the constant density star found in [2], [19] and [9]. We prove that the lower branch of weak-field solutions is stable whereas the upper branch is unstable.…”
Section: Introductionmentioning
confidence: 93%
“…For the LS projection operators and splittings of the range and domain we follow the notation of [12] section 1.4-1.7, which is equivalent to [19]. In particular we have that 15) where N denotes the kernel space and R the range of the linearisation.…”
Section: Stability Of Solutions Via Liapunov-schmidt Reductionmentioning
confidence: 99%
See 1 more Smart Citation